Review on Traditional Use of Nephroprotective Plants in Kerala - Praseeda KG (Journal of Global Pharma Technology, 2019)
Our mother nature is an abundant treasure of medicinal plants. Many of the plants have active constituents like alkaloids, benzoquinones, catechols, carotenoids, flavonoids, glycosides, flavanol glycosides, steroid glycosides, glycoalkaloids, terpenoids, monoterpenoids, diterpenoids, triterpene saponins, sterols and polyphenols which are proved to be having tissue rejuvenation property. Which can be made use in critical conditions like nephropathy which can be curable only with kidney transplantation or dialysis, which are even unaffordable to common man. It will be very useful to isolate active ingredients from easily available medicinal plants which can be effectively used for conditions like Chronic Kidney Disease. India is a country which extensively follows different forms of medications like allopathy, Ayurveda, siddha and unani among them traditional system of medicine is considered to be pretty much important. The biodiversity of India helps traditional healers to explore vast possibility of it. Modern medicine gets ample support by evaluating and isolating natural, semisynthetic, and synthetic derivatives of effective phytoconstituents of herbs. The information’s regarding such medicinal plants is exclusively possessed by certain tribal communities all over India. This article also points towards some plants used by traditional healers of different tribal communities of Kerala.Keywords: Nephroprotective, Herbal medicine, Tribal communities.